2000
DOI: 10.1037/0021-843x.109.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in schizophrenia: Further investigation of generalized versus specific deficit models.

Abstract: In this study, the authors examined the nature of emotion perception in schizophrenia. Two samples of people with schizophrenia, one receiving acute care for a recent exacerbation of symptoms and the other receiving extended care, were compared with a nonclinical control group on emotion perception and general perception measures. The nonclinical control group obtained the highest scores on all of the study measures, and the acutely ill group obtained the lowest scores. Furthermore, the acutely ill sample had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 14 publications
7
79
0
11
Order By: Relevance
“…For example, a recent study reported that schizophrenia patients in acute stages of illness demonstrated a specific affect recognition deficit, but chronic schizophrenia patients demonstrated a general face processing deficit (Penn et al, 2000). However, others who have investigated stages and characteristics of schizophrenic illness such as number of hospitalizations, duration of hospital stay, and chronicity of illness have found no specific association with affect recognition abilities (Salem et al, 1996;Addington and Addington, 1998).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a recent study reported that schizophrenia patients in acute stages of illness demonstrated a specific affect recognition deficit, but chronic schizophrenia patients demonstrated a general face processing deficit (Penn et al, 2000). However, others who have investigated stages and characteristics of schizophrenic illness such as number of hospitalizations, duration of hospital stay, and chronicity of illness have found no specific association with affect recognition abilities (Salem et al, 1996;Addington and Addington, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Most of these investigations have found that schizophrenia patients have defi-cits in both facial and vocal affect recognition (e.g. Archer et al, 1994;Baudouin et al, 2002;Borod et al, 1993;Edwards et al, 2001;Feinberg et al, 1986;Heimberg et al, 1992;Mandal et al, 1998;Penn et al, 2000;Schneider et al, 1995;Walker et al, 1984), and that these deficits are not related to age, gender, medication status or neuroleptic dose (Kline et al, 1992;Poole et al, 2000;Salem et al, 1996;Schneider et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two studies examined sex differences in FEP in adult samples of chronically ill people with schizophrenia. The majority of these studies (n = 19) did not find sex differences in FEP, either on identification tasks [31][32][33][34][35][36][37][38][39][40][41] , discrimination tasks [42,43] , or in studies that included both task types [44][45][46][47][48][49] . Three studies included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] found sex differences in FEP performance on identification tasks in adults with chronic schizophrenia.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%
“…Focusing on facial emotion perception many studies could show deficits in the processing of emotional facial expressions in schizophrenia patients (Feinberg et al, 1986;Heimberg et al, 1992;Kohler et al, 2003;Mueser et al, 1997;Penn et al, 2000;Schneider et al, 1995Schneider et al, , 2006. A more detailed inspection of these impairments revealed that although the sensitivity to detect a specific emotion was preserved, the specificity was affected, ie schizophrenia patients exhibited problems in rejecting faces with other than the target emotional expression .…”
Section: Introductionmentioning
confidence: 99%